Negotiating the ground: 'mobilizing' a divided field site in the 'post-conflict' city. Issue 6 (2nd November 2018) - Hocking, Bree T.; Sturgeon, Brendan; Whyatt, Duncan; Davies, Gemma; Huck, Jonny; Dixon, John; Jarman, Neil; Bryan, Dominic
ABSTRACT: While an exploration of mobility patterns in 'post-conflict' societies has much to tell us about how division is produced through ordinary activities, less work has considered the practical application of a mobilities 'lens' during fieldwork in such contexts. Negotiating the ground in highly polarized contexts presents a unique array of challenges, but also offers opportunities to make use of mobile methodologies. This paper discusses the advantages of GPS-based technologies and walking interviews to a recent activity-space segregation study in Belfast, Northern Ireland, and reflects on methodological issues posed by the 'post-conflict' field site.